Synthesis and Properties of Anion Exchangers Derived from Chloromethyl Styrene Codivinylbenzene and Their Use in Water Treatment. (31st May 2010) - Ezzeldin, Hesham A.; Apblett, Allen; Foutch, Gary L.
Abstract : Amination of vinylbenzyl chloride-divinylbenzene (VBC-DVB) copolymers is an effective method for preparation of ion-exchange resins. Conventionally, the starting polymer is produced by chloromethylation of a styrene-divinylbenzene copolymer that utilizes chloromethyl methyl ether, a known carcinogen. An alterative approach is to copolymerize vinylbenzyl chloride with divinylbenzene to generate the necessary VBC-DVB. This method provides precise control over the density of the ion-exchange groups. The regiochemistry of the vinylbenzyl chloride methods was realized using solvent-ion exchange groups. In this investigation, an improved solvent system was found for the preparation of anion exchange resins by the vinylbenzyl chloride route. The effectiveness of amination of the intermediate VBC-DVB polymers with a variety of trimethylamine reagents was investigated, and ethanolic trimethylamine produced the highest degree of amination. These resulting ion-exchange polymers were characterized by a variety of techniques such as analytical titrations, nitrogen analysis, Fourier transform infrared spectroscopy and thermal gravimetric analysis. Testing of these copolymers for breakthrough was performed. The results indicate that these anion exchangers have a meaningful increase in thermal stability over commercial anionic exchange beads.